Reproducibility of the point connection technique for measuring hallux valgus angles using a smartphone application - Cortês Padilha, Luis Felipe; Almeida de Sousa Nogueira , Thomás; Povoleri Marano, Bruno; Monteiro Camisão, Rodrigo; Costa Barreto Brígido, João Victor; Almeida Ribeiro de Miranda, Vitor (Journal of the Foot & Ankle, 2022)
Objective: A) To evaluate the reliability of a new technique for the measurement of both intermetatarsal and hallux valgus angles. B) To evaluate whether this technique can be performed with the aid of a smartphone application. Methods: Preoperative radiographs of 30 patients were evaluated by four observers, two experienced surgeons and two surgeons in training. They performed measurements of the intermetatarsal angle and hallux valgus angle using the classical method and using the new method, both employing a goniometer and a smartphone application. Analysis of agreement was done by quantifying the raw agreement and calculating the intraclass correlation coefficient (ICC). Results: The hallux valgus angle presented excellent agreement (ICC>0.80) both using the traditional method and the point connection method, while the intermetatarsal angle presented a very good agreement (0.60<ICC≤0.80) in both methods. Conclusion: The point connection technique showed good concordance rates when measured by smartphone applications, although it did not prove to be superior to the traditional one. Level of Evidence II; Diagnostic Study; Development of Diagnostic Criteria.